Physical Function and Survival in Older Adults: A longitudinal study accounting for time-varying effects. (September 2021) - Karunananthan, Sathya; Moodie, Erica E M; Bergman, Howard; Payette, Hélène; Diehr, Paula H; Wolfson, Christina
Highlights: Physical function changes over time among older adults We examined the effects of time-varying measures of physical function on survival Higher gait speed was associated with increased one-year survival among women Gait speed was not associated with one-year survival in men Grip strength was not associated one-year survival in women or men Abstract: Purpose of the study: Variation in physical function in older adults over time raises several methodological challenges in the study of its association with survival, many of which have largely been overlooked in previous studies. The objective of this study is to examine the relationship between time-varying measures of physical function and survival in men and women aged 70 years and over, while accounting for the time-varying effects of health and lifestyle characteristics. Methods: 1, 846 women and 1, 245 men in the Cardiovascular Health Study followed annually for up to 10 years beginning at age 70-74 years were included. We estimated the effect of gait speed and grip strength on survival over the subsequent year, using age as the timescale. Results: A 0.1m/s higher gait speed was associated with a 12% decrease in the likelihood of death in the subsequent year among women (HR 0.88, 95% CI 0.82-0.94). There was no statistically significant effect of gait speed on survival among men (HR 0.97, 95% CI 0.91 to 1.03), or of grip strength on survival among women (HR 0.97, 95% CI 0.95-1.00) or men (HR 0.99, 95% CI 0.97-1.01), over one year. Conclusions: Upon using time-varying measures of physical function while accounting for time-varying effects of health and lifestyle characteristics, higher gait speed was associated with increased survival among the women in our study. We found no evidence of an association between gait speed and one-year survival in men, or between grip strength and one-year survival in women or men.